Perceived outcomes of medical teaching institute reforms: insights from management, faculty, and administration in Pakistani tertiary health care - Wajiha Qamar; Mehran Qayum; Waqar-un Nisa; Asma Ali (BMC, 2024)
Abstract Objective The study aims to explore the perceived outcomes of Medical Teaching Institution (MTI) reforms on autonomy and overall performance within tertiary healthcare institutions in Khyber Pakhtunkhwa (KP) province, Pakistan. Methodology A cross-sectional study was carried out from September 2023 to March 2024, involving interviews with frontline staff, administrative personnel, and senior management within MTI-affiliated institutions. The methodology employed, using both qualitative and quantitative data analysis techniques. Results The study showed that institutional staff members' knowledge and understanding of the MTI changes differed. Some observed very minor adjustments, while others saw advances in hospital operations and service delivery. Administrative complexity, political meddling, and resource allocation problems were noted as challenges. Positive results were also observed, though, and they included improved infrastructure, possibilities for staff training, and decision-making procedures. Conclusion Despite significant improved, there are still challenges, such as inconsistent staff comprehension, mixed impacts on service delivery, resource allocation issues, and political meddling. Addressing these issues necessitates improved communication, continuous evaluation, and coordinated efforts to improve administrative systems and obtain consistent funding.